Public Transportation Service Performance: (A Critical Review of Cirebon Bus Rapid Transit) - Fadhilah, Amiroh Nur; Aryana, Regina; Khumayah, Siti; Rahmayanti, Rahmayanti (Indonesian Journal of Advanced Research, 2025)
This study analyzes the performance of the Trans Cirebon Bus Rapid Transit (BRT) service as a modern and sustainable public transportation initiative. Using a descriptive qualitative method and Colin Talbot’s performance model, data were collected through observation, interviews, and document analysis, with triangulation ensuring data validity. Findings show that while BRT Trans Cirebon contributes to mass transportation, challenges remain, including limited routes, low public interest, and continued reliance on private vehicles. Key actors include the Cirebon City Government, PD. Pembangunan, and private partner PT BIG. Improving service effectiveness requires good governance, transparency, accountability, and public participation. A more comprehensive strategy—enhancing management, infrastructure, operations, and digital integration—is needed to optimize the BRT system and reduce private vehicle use.